A four-layer structure scaffold for bone tissue regeneration and a preparation method thereof

CN117582558BActive Publication Date: 2026-10-27TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311611329.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2026-10-27
Estimated Expiration
2043-11-29

AI Technical Summary

Technical Problem

然而,很少报道超过三个层次的层次结构,如宏观、微观和纳米多孔支架

Benefits of technology

本发明制备的四层次结构骨组织再生用支架有利于细胞穿透、血管化、骨传导和骨诱导,最终实现骨组织修复,分层支架的抗压强度为2MPa左右,与松质骨相匹配,旨在减轻应力屏蔽效应,且有良好的生物相容性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117582558B_ABST
    Figure CN117582558B_ABST
Patent Text Reader

Abstract

The application aims to provide a four-layer structure bone tissue regeneration scaffold and a preparation method thereof, and belongs to the technical field of biomedical materials, and the preparation steps are as follows: ① a first layer structure reverse template is printed by 3D printing; ② the 3D printed template is placed into a cold finger, a prepared slurry is poured to immerse the template, and directional freezing is carried out; ③ the frozen sample is subjected to freeze-drying sublimation ice removal; ④ the sublimated sample is sintered to obtain a four-layer structure tricalcium phosphate (FH-TCP) scaffold. The four-layer structure tricalcium phosphate scaffold (FH-TCP) is conducive to cell penetration, vascularization, bone conduction and bone induction, the compressive strength of the layered scaffold is about 2 MPa, which is matched with cancellous bone, aims to reduce the stress shielding effect, and has good biocompatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials technology, specifically relating to a four-layer structure scaffold for bone tissue regeneration and its preparation method. Background Technology

[0002] Tissue engineering aims to repair damaged organs and tissues or provide replacements for these defects. Despite significant progress, creating a native environment capable of correctly replicating damaged tissue remains a major challenge. To provide the necessary support for cells, maintain cell viability, and predetermine the shape required for regenerated tissue, scaffolds need to be designed in three dimensions, from macroscopic to nanoscale.

[0003] Bone tissue is a vital component of the human body. Early bone regeneration scaffolds were manufactured using completely dense bulk materials or films through casting or spinning methods, creating a single-pore structure to promote tissue growth. For example, porous scaffolds with pore sizes greater than 300 μm facilitated vascularization and inward bone growth, while micropore scaffolds of 50–150 μm promoted osteoid formation and inward growth of mineralized bone. However, a single-pore structure cannot meet the multifunctional requirements of tissue engineering; a layered structure is often preferred. Different characteristics can be combined into a single scaffold to achieve optimal osteogenic performance. Generally, micropores trap cells within their lumen, helping to reduce neutrophil responses and further promoting macrophage polarization, while macropores and interconnectivity promote vascularization and ultimately tissue repair.

[0004] Several fabrication processes have been developed to control the pore morphology and size of scaffolds, including 3D printing, electrospinning, cryogenic casting, two-photon polymerization, and foam templates. These processes allow for the creation of one- or two-level hierarchical structures, such as macro / nano and micro / nanoporous scaffolds. However, hierarchical structures with more than three levels, such as macro, micro, and nanoporous scaffolds, are rarely reported. Summary of the Invention

[0005] The purpose of this invention is to provide a four-layer structure scaffold for bone tissue regeneration and its preparation method. The four-layer structure is conducive to cell penetration, vascularization, osteoconduction and osteoinduction, and ultimately achieves bone tissue repair. The compressive strength of the layered scaffold is about 2 MPa, which is matched with cancellous bone. It aims to reduce the stress shielding effect and has good biocompatibility.

[0006] The present invention adopts the following technical solution: A four-layer structure scaffold for bone tissue regeneration, wherein the scaffold is a tricalcium phosphate (FH-TCP) scaffold with a four-layer structure, and the FH-TCP scaffold has a four-layer structure at the macro, micro and nano scales.

[0007] Furthermore, the four-level structure is as follows: First layer: 3D printing template: By reverse-copying templates with four different internal structures, including icosagon, dodecagon, octahedron, and gyroid, the first-level hierarchical structure at the macroscopic scale is achieved. After heat treatment, these 3D printing templates are completely removed by carbonization and thermal decomposition, leaving the macroscopic structure we need.

[0008] Second layer: Cryogenic layered structure: The slurry is immersed in the 3D printing template and then directionally frozen to form 20μm directional sheet-like pores in the template, thus forming the second layer structure.

[0009] The third layer: sintering-induced nanostructures: high temperature causes atoms to diffuse through the boundaries of the particles, loosely fusing the particles together to form a nanoscale porous structure.

[0010] Fourth layer: Mesoporous hydroxyapatite particles: Inherited from the raw material of the scaffold material, namely mesoporous hydroxyapatite particles.

[0011] Furthermore, the scaffold has: highly interconnected macropores with a pore size of 0.2 mm to 3 mm, micropores with a pore size of 1 to 70 μm, nanopores with a pore size of 100 to 300 nm, and mesopores with a pore size of 5 to 10 nm. A method for preparing a four-layered bone tissue regeneration scaffold includes the following steps: The first step is to design the reverse template of the first-level structure using computer-aided design software and generate it through photopolymerization 3D printing. The second step involves using mesoporous hydroxyapatite as a precursor to synthesize mesoporous hydroxyapatite (HA) particles via a hydrothermal method. The third step involves adding the synthesized mesoporous hydroxyapatite and additives to deionized water in a certain proportion and stirring magnetically to form a suspension slurry with a volume fraction of 1% vol to 50% vol. The fourth step is to place the 3D-printed reverse template into the mold, slowly pour the slurry into the mold to immerse the reverse template, perform directional freezing, and then perform low-temperature treatment on the sample. Fifth, after the sample has undergone low-temperature treatment, sublimation de-icing is performed; The sixth step is to sinter the sublimated sample to obtain a four-layer tricalcium phosphate (FH-TCP) scaffold.

[0012] Furthermore, the 3D printed reverse template mentioned in the first step includes four structures: icosagon, dodecagon, octahedron, and gyroid.

[0013] The 3D printing template has its porosity of 60% in the first layer structure by modifying its size parameters; the 3D printing material is a photopolymer.

[0014] Furthermore, the hydrothermal synthesis of mesoporous hydroxyapatite described in the second step includes the following steps: (1) Disperse Na2HPO4 and hexadecyltrimethylammonium bromide (CTAB) in deionized water to form 100 ml solution I (the mass fraction of Na2HPO4 does not exceed 30%, and the mass ratio of CTAB to Na2HPO4 is 1:1), and adjust the pH of solution I to 12 with 1 M sodium hydroxide solution; (2) Add CaCl2 to deionized water to form solution II (ensure that the Ca in solution II is in a certain concentration). 2+ Concentration and PO4 in solution I 3- (The phosphate molar ratio is 1.67). (3) After stirring, solution II is introduced dropwise into solution I to obtain a mixed solution; (4) The obtained mixed solution was stored at 150°C for 12 hours in the oven of the hydrothermal reactor and then cooled to room temperature; (5) The precipitate was obtained by centrifugation. The precipitate was washed 5 times with deionized water and 1 time with ethanol in a centrifuge. (6) The precipitate was heated to 550°C to obtain nano-sized HA particles.

[0015] Furthermore, the additives mentioned in the third step include 1 wt% polyethylene glycol, 1 wt% poly(2-ethyl-2-oxazoline) and 4 wt% Darvan 811, with a magnetic stirring speed of 1-1000 r / min and a stirring time of 12-48 h.

[0016] Furthermore, the directional freezing rate in the fourth step is 1-10 mm / min, and the low-temperature treatment involves keeping the sample at -10°C for 24 hours to balance the internal temperature and reduce internal stress.

[0017] Furthermore, the sublimation de-icing described in step five involves placing the sample in a freeze dryer at 310 Pa for 24 hours to ensure complete de-icing.

[0018] Furthermore, in the sintering process described in step six, the scaffold undergoes three stages of heating and three stages of isothermal treatment, with the heating and isothermal treatments alternating. Specifically, the temperature is increased to 500°C at 10°C / min from room temperature and held for 50 min; then increased to 800°C at 10°C / min and held for 50 min; finally increased to 1200°C at 10°C / min and held for 50 min; and then cooled to room temperature to obtain the FH-TCP scaffold.

[0019] The beneficial effects of this invention are as follows: The four-layered scaffold for bone tissue regeneration prepared in this invention facilitates cell penetration, vascularization, osteoconduction, and osteoinduction, ultimately achieving bone tissue repair. The compressive strength of the layered scaffold is about 2 MPa, which matches that of cancellous bone, aiming to reduce stress shielding effect and has good biocompatibility. Attached Figure Description

[0020] Figure 1 The 3D printing templates prepared in Examples 1-4 of this invention; Figure 2 TEM images of HA particles prepared in Example 5 of the present invention: a: TEM image of the size and typical shape of HA particles; b: independent mesopores (5~10 nm) of HA particles. Figure 3 This is a schematic diagram of the directional freezing process of the present invention; Figure 4 SEM and TEM images of the four-layer structure of the stent prepared in Embodiment 6 of the present invention.

[0021] Figure 5 Cross-sectional views of the stents prepared in Examples 6-9 and Comparative Example 1 of the present invention. Detailed Implementation

[0022] The invention will be further illustrated below with specific examples: A schematic diagram of the directional refrigeration device used in the example is shown below. Figure 3 As shown, the bottom is a frozen surface and the top is a cylindrical injection hole (cold finger). First, the 3D printing template is placed into the cold finger, and then the slurry is poured in to immerse the template. Figure 3 The right side shows an enlarged view of the four-layer structure of the FH-TCP scaffold: 3D printed template, freeze-cast induced layered structure, sintering induced nanostructure, and mesoporous hydroxyapatite particles.

[0023] Example 1: Preparation of 3D Printing Template (1) Design the spiral (Gyroid) support template using CAD software; (2) Prepare printing materials; (3) Print using a photopolymer 3D printer.

[0024] Example 2: Preparation of 3D Printing Template The preparation was carried out in accordance with Example 1, except that in step (1), an icosagon template was designed using CAD software.

[0025] Example 3: Preparation of 3D Printing Template The preparation was carried out in accordance with Example 1, except that a dodecagon template was designed using CAD software in step (1).

[0026] Example 4: Preparation of 3D Printing Template The preparation was carried out in accordance with Example 1, except that an octahedron template was designed using CAD software in step (1).

[0027] Example 5: Preparation of mesoporous hydroxyapatite (HA) (1) Disperse Na2HPO4 and hexadecyltrimethylammonium bromide (CTAB) in deionized water to form solution I, and adjust the pH of solution I to 12 with 1M sodium hydroxide solution; (2) Add CaCl2 to deionized water to form solution II; (3) After vigorous stirring, introduce solution II into solution I drop by drop; (4) The obtained solution was stored at 150°C for 12 hours in the oven of the hydrothermal reactor and then cooled to room temperature. (5) The precipitate was obtained by centrifugation. The precipitate was washed 5 times with deionized water and 1 time with ethanol in a centrifuge. (6) The precipitate was heated to 550°C to remove the template of CTAB, and then cooled to room temperature to obtain HA particles.

[0028] The HA particles obtained in this example were characterized using TEM. Figure 2 As shown in (a), the HA particles are rod-shaped single crystals, and the length of the rods is proportional to the synthesis time and temperature; as Figure 2 As shown in (b), independent mesopores (5~10 nm) can be observed distributed around the surface formed by the CTAB (hexadecyltrimethylammonium bromide) template, indicating that the scaffold has a fourth layer structure.

[0029] Example 6: Preparation of a four-layer tricalcium phosphate (FH-TCP) scaffold (1) The mesoporous hydroxyapatite in Example 5 was mixed with deionized water, and 1 wt% polyethylene glycol, 1 wt% poly(2-ethyl-2-oxazoline) and 4 wt% Darvan 811 were added. The mixture was magnetically stirred at 500 r / min for 24 h to obtain a slurry. (2) The spiral (Gyroid) template prepared in Example 1 was placed in a custom mold, and the slurry obtained in step (1) was poured into the mold to immerse the template. The sample was obtained by directional freezing at a rate of 3.175 mm / min. The sample was then kept at -10℃ for 24 h to balance the internal temperature and reduce the internal stress. (3) Sublimate the sample in a freeze dryer at 310 Pa for 24 hours to fully de-ice; (4) The sublimated sample was sintered, specifically by heating at 10℃ / min to 500℃ and holding for 50 min; heating at 10℃ / min to 800℃ and holding for 50 min; heating at 10℃ / min to 1200℃ and holding for 50 min; and cooling to room temperature to obtain the FH-TCP scaffold. During the sintering process, due to the low melting point of the 3D printing template material, it was completely removed by carbonization and thermal decomposition during sintering, leaving the required first-level structure, i.e., the macroscopic structure.

[0030] The FH-TCP scaffold obtained in this embodiment was characterized by SEM, TEM, and optical microscopy, such as... Figure 4 As shown, the FH-TCP scaffold possesses highly interconnected macropores with pore sizes ranging from 0.2 mm to 3 mm, micropores with pore sizes from 1 to 70 μm, nanopores with pore sizes from 100 to 300 nm, and mesopores with pore sizes from 5 to 10 nm. It exhibits a four-layered structure: macropores from removed 3D printing templates, a layered structure induced by freeze-casting, a nanostructure induced by sintering, and mesoporous hydroxyapatite particles.

[0031] Example 7: Preparation of a four-layer tricalcium phosphate (FH-TCP) scaffold The preparation was carried out in accordance with Example 6, except that in step (2), the icosagon template prepared in Example 2 was placed in a custom-made freezing device cold finger, and the slurry obtained in step (1) was poured into the cold finger to immerse the template.

[0032] Example 8: Preparation of a four-layer tricalcium phosphate (FH-TCP) scaffold The preparation was carried out in accordance with Example 6, except that in step (2), the dodecagon template prepared in Example 3 was placed in a custom-made freezing device cold finger, and the slurry obtained in step (1) was poured into the cold finger to immerse the template.

[0033] Example 9: Preparation of a four-layer tricalcium phosphate (FH-TCP) scaffold The preparation was carried out in accordance with Example 6, except that in step (2), the octahedron template prepared in Example 4 was placed in a custom-made freezing device cold finger, and the slurry obtained in step (1) was poured into the cold finger to immerse the template.

[0034] Comparative Example 1: Preparation of a comparative tricalcium phosphate (C-TCP) scaffold (1) The mesoporous hydroxyapatite in Example 5 was mixed with solvent water, and 1 wt% polyethylene glycol, 1 wt% poly(2-ethyl-2-oxazoline) and 4 wt% Darvan 811 were added. The mixture was magnetically stirred at 500 r / min for 24 h to obtain a slurry. (2) Pour the slurry obtained in step (1) into a cold finger and freeze it at a rate of 3.175 mm / min to obtain a sample. Then keep the sample at -10℃ for 24 hours to balance the internal temperature and reduce the internal stress. (3) Sublimate the sample in a freeze dryer at 310 Pa for 24 hours to fully de-ice; (4) The sublimated sample was sintered by heating at 10℃ / min to 500℃ and holding for 50min; heating at 10℃ / min to 800℃ and holding for 50min; heating at 10℃ / min to 1200℃ and holding for 50min; and cooling to room temperature to obtain the C-TCP scaffold.

[0035] Compared with the FH-TCP stents prepared in Examples 6, 7, 8 and 9, the C-TCP stent prepared in Comparative Example 1 is a simple cryo-cast stent, lacking the first-level structure.

[0036] The biocompatibility of all prepared scaffolds was tested using the MTT assay. After 7 days of culture, the cell viability of all prepared scaffolds was higher than that of the empty scaffolds, indicating that they enhanced cell proliferation and possessed good biocompatibility. Scaffolds with icosagonal, octahedron, and gyroid structures prepared in Examples 6, 8, and 9 showed higher cell viability and better biocompatibility compared to the scaffold without a first-level structure prepared in Comparative Example 1. This is because the first-level structure provides channels for nutrient exchange and may have a guiding effect, as previously found, promoting cell penetration into the scaffold interior.

[0037] The above description is merely a preferred embodiment of the present invention, and the scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that modifications or improvements made by those skilled in the art without departing from the principles of the present invention are all within the scope of protection claimed by the present invention.

Claims

1. A four-layered scaffold for bone tissue regeneration, characterized in that: The scaffold is a tricalcium phosphate scaffold with a four-layer structure; The four-layer structure consists of: a 3D-printed reverse template, a cryogenically cast layered structure, a sintering-induced nanostructure, and mesoporous hydroxyapatite particles. The scaffold has: highly interconnected macropores with a pore size of 0.2~3mm, micropores with a pore size of 1~70μm, nanopores with a pore size of 100~300nm, and mesopores with a pore size of 5~10nm. The mesoporous hydroxyapatite particles were synthesized by a hydrothermal method.

2. A method for preparing a four-layered bone tissue regeneration scaffold as described in claim 1, characterized in that: Includes the following steps: The first step is to design the reverse template of the first-level structure using computer-aided design software and generate it through photopolymerization 3D printing. The second step involves synthesizing mesoporous hydroxyapatite particles using mesoporous hydroxyapatite as a precursor via a hydrothermal method. This process includes the following steps: (1) Disperse Na2HPO4 and hexadecyltrimethylammonium bromide in deionized water to form 100 ml solution I, where the mass fraction of Na2HPO4 does not exceed 30%, the mass ratio of hexadecyltrimethylammonium bromide to Na2HPO4 is 1:1, and adjust the pH of solution I to 12 with 1 M sodium hydroxide solution; (2) Add CaCl2 to deionized water to form solution II, ensuring that the Ca in solution II is within the range of 100%. 2+ Concentration and PO4 in solution I 3- The phosphate molar ratio is 1.67; (3) After stirring, solution II is introduced dropwise into solution I to obtain a mixed solution; (4) The obtained mixed solution was stored at 150°C for 12 hours in the oven of the hydrothermal reactor and then cooled to room temperature; (5) The precipitate was obtained by centrifugation. The precipitate was washed 5 times with deionized water and 1 time with ethanol in a centrifuge. (6) The precipitate was heated to 550°C to obtain nano-sized mesoporous hydroxyapatite particles; The third step involves adding the synthesized mesoporous hydroxyapatite and additives to deionized water and magnetically stirring to form a suspension slurry with a volume fraction of 1% vol to 50% vol. The fourth step is to place the 3D-printed reverse template into the mold, and then slowly pour the slurry into the mold to immerse the reverse template. The slurry is then frozen using directional freezing technology. Fifth, after the sample has undergone low-temperature treatment, sublimation de-icing is performed; The sixth step is to sinter the sublimated sample to obtain a four-layer tricalcium phosphate scaffold.

3. The method for preparing a four-layered bone tissue regeneration scaffold according to claim 2, characterized in that: The reverse template for 3D printing mentioned in the first step includes four structures: icosahedron, dodecagon, octahedron, and spiral.

4. The method for preparing a four-layered bone tissue regeneration scaffold according to claim 2, characterized in that: The additives mentioned in the third step include 1 wt% polyethylene glycol, 1 wt% poly(2-ethyl-2-oxazoline), and 4 wt% Darvan 811. The magnetic stirring speed is 1-1000 r / min, and the stirring time is 12-48 h.

5. The method for preparing a four-layered bone tissue regeneration scaffold according to claim 2, characterized in that: In the fourth step, the freezing rate of the freezing equipment is 3.175 mm / min. The low-temperature treatment involves keeping the sample at -10°C for 24 hours to balance the internal temperature and reduce internal stress.

6. The method for preparing a four-layered bone tissue regeneration scaffold according to claim 2, characterized in that: The sublimation de-icing step described in step 5 involves placing the sample in a freeze dryer at 310 Pa for 24 hours to ensure complete de-icing.

7. The method for preparing a four-layered bone tissue regeneration scaffold according to claim 2, characterized in that: In step six, the sintering process involves three stages of heating and three stages of isothermal treatment, with the heating and isothermal treatments alternating. Specifically, the temperature is increased to 500℃ at 10℃ / min from room temperature and held for 50 min; then increased to 800℃ at 10℃ / min and held for 50 min; finally increased to 1200℃ at 10℃ / min and held for 50 min; and then cooled to room temperature to obtain a four-layer tricalcium phosphate scaffold.

Citation Information

Patent Citations

  • Bio-ceramic stent and applications thereof

    CN110227178A

  • KR1017944970000B1